SENSITIVITY TEST OF VIBRIO sp BACTERIA ISOLATED FROM DUMAI SEA WATERS TO ANTIBIOTICS (CIPROFLOXACIN, ERYTROMYCIN AND STREPTOMYCIN) - Fitri, Febi Anisa; FE, Feliatra; Yoswati, Dessy (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2020)
The research was conducted from Feb until April 2019. The purpose of this study was to examine the resistance of Vibrio sp bacteria toward antibiotics (ciprofloxacin, streptomycin and erythromycin) isolated from Dumai sea waters. The spread of Vibrio sp bacteria has been found in sea waters, Vibrio sp bacteria have been found on the surface of faecal contaminated water and the existence of the population is related to organic waste disposal. Antibiotic susceptibility test was performed using Kirby-Bauer method. Resistance test showed that isolated V2, V9, V11, V13, V19, V23, V24 dan V28 were resistant to antibiotic ciprofloxacin, streptomycin and erythromycin with inhibitory zones ranging from 7,1 to 31,7 mm. Isolated V2 and V9 are resistant to erythromycin, isolated V11, V13, V19, V23 and V28 are resistant to streptomycin and isolated V24 is resistant to ciprofloxacin.